2019
DOI: 10.1177/0284185119834687
|View full text |Cite
|
Sign up to set email alerts
|

Distal radius fractures and radiographic assessment: a systematic review of measurement accuracy

Abstract: Background Distal radius fracture characterization and treatment are mainly based on radiographic measurements but with contradictory findings on the correlation of those measurements to clinical outcome. Before applying radiographic measurement to the treatment decision and before correlating the measurements to clinical outcome, an accuracy of measurements must be established. Purpose To summarize existing evidence on accuracy of the radiographic measurements of: (i) dorsal/volar tilt of the distal radius;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A thorough review on the radiographic parameters of distal radius fractures showed marked variability in the actual description of performing the measurements (Lalone et al., 2015). In a recent review on the evidence regarding the accuracy of the parameters, five of 5908 publications were found to be eligible (Jensen et al., 2019). The study concluded that there is no evidence available to support the accuracy of the radiographic measurements.…”
Section: Discussionmentioning
confidence: 99%
“…A thorough review on the radiographic parameters of distal radius fractures showed marked variability in the actual description of performing the measurements (Lalone et al., 2015). In a recent review on the evidence regarding the accuracy of the parameters, five of 5908 publications were found to be eligible (Jensen et al., 2019). The study concluded that there is no evidence available to support the accuracy of the radiographic measurements.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is lack of evidence supporting the correlation between clinical outcomes of the fracture and degree of radiographic deformity. 40 In a recent randomized study, Plant et al reported radiographic parameters as poor predictors of satisfactory functional outcomes and raised concerns about the use of radiological parameters to determine management. 41…”
Section: Discussionmentioning
confidence: 99%
“…However, there is lack of evidence supporting the correlation between clinical outcomes of the fracture and degree of radiographic deformity. 40 In a recent randomized study, Plant et al reported radiographic parameters as poor predictors of satisfactory functional outcomes and raised concerns about the use of radiological parameters to determine management. 41 Initial postoperative superiority of VLP fixation in terms of DASH, grip strength, and ROM outcomes could be explained by immediate commencement of early rehabilitation protocol after surgery, anatomical restoration of joint, the surface and superior biochemical properties of volar plates that are capable of sustaining physiological loads of early active wrist motion.…”
Section: Discussionmentioning
confidence: 99%
“…In order to promote blood circulation and eliminate inflammatory edema, we choose the density wave with a frequency of 2/100 HZ. Previous guidelines developed by ASSH and several studies have shown that ulnar variability is an accurate radiological predictor of functional outcome [ 48 , 49 ]. We will calculate the changes in ulnar positive variance before and after treatment in both groups of patients.…”
Section: Discussionmentioning
confidence: 99%